2021
DOI: 10.1103/physrevb.103.035135
|View full text |Cite
|
Sign up to set email alerts
|

Ambient-pressure Dirac electron system in the quasi-two-dimensional molecular conductor α(BETS)2I3

Abstract: We investigated the precise crystal structures and electronic states in a quasi-two-dimensional molecular conductor α-(BETS)2I3 at ambient pressure. The electronic resistivity of this molecular solid shows a metal-to-insulator (MI) crossover at 𝑇 MI = 50 K. Our x-ray diffraction and 13 C nuclear magnetic resonance experiments revealed that α-(BETS)2I3 maintains the inversion symmetry below 𝑇 MI . The first-principles calculations found a pair of anisotropic Dirac cones at a general k-point, where the degener… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 84 publications
2
40
1
Order By: Relevance
“…The Arrhenius plots of ∆σ (Figure 6b) show that unlike in α-(BEDT-TTF) 2 I 3 , the activation energy near the transition temperature significantly decreases with increasing positive V G . The mechanism is unclear because the insulating state of α-(BETS) 2 I 3 is not a simple charge-ordered state, and the insulating mechanism is under debate [14][15][16]. However, the present results may provide clues to understanding the insulating phase of this compound.…”
Section: α-(Bets) 2 Imentioning
confidence: 79%
See 3 more Smart Citations
“…The Arrhenius plots of ∆σ (Figure 6b) show that unlike in α-(BEDT-TTF) 2 I 3 , the activation energy near the transition temperature significantly decreases with increasing positive V G . The mechanism is unclear because the insulating state of α-(BETS) 2 I 3 is not a simple charge-ordered state, and the insulating mechanism is under debate [14][15][16]. However, the present results may provide clues to understanding the insulating phase of this compound.…”
Section: α-(Bets) 2 Imentioning
confidence: 79%
“…Therefore, it is considered that the electronic state of α-(BETS) 2 I 3 is similar to that of moderately pressurized α-(BEDT-TTF) 2 I 3 . However, recent X-ray diffraction and 13 C nuclear magnetic resonance experiments revealed that α-(BETS) 2 I 3 maintains inversion symmetry below the transition temperature [14]. These results imply a different insulating mechanism from simple charge ordering (the spin-orbit interaction may play an important role).…”
Section: Methodsmentioning
confidence: 93%
See 2 more Smart Citations
“…Consequently, if the coupling through donors B could be reinforced, for instance through applied pressure, and the metallic state could be stabilized, the Fermi level would occur at the K point and thus would coincide with a Dirac cone which could lead to the exotic transport properties predicted for this situation. 35 Among molecular conductors, only (EDT-TTF-CONH 2 ) 6 [Re 6 Se 8 (CN) 6 ], 36,37 a-(BEDT-TTF) 2 I 3 under pressure, 38 [Pd(dddt) 2 ] (dddt = 5,6-dihydro-1,4-dithiin-2,3-dithiolate) under pressure, 39 [Pt(dmdt) 2 ] (dmdt = dimethyl-tetrathiafulvalenedithiolate) 40 and, very recently, a-(BETS) 2 I 3 (BETS = bis (ethylenedithio)-tetraselenafulvalene) 41 have been previously shown to exhibit such an uncommon electronic feature. Unfortunately, our measurements suggest that in the present salts the electrons remain localized at the pressures we could reach.…”
Section: Synthesis and Structure Of The Radical Cation Saltsmentioning
confidence: 99%